DETERMINAN FAKTOR YANG MEMPENGARUHI LITERASI KEUANGAN PELAKU UMKM DI KOTA AMBON - Restia Christianty; Teddy Christianto Leasiwal (Pattimura Proceeding, 2022)
The purpose of this research is to analyze the factors that influence the financial literacy of micro, small and medium enterprises (MSMEs) in Ambon City. A quantitative approach with verification research is used in this study. Meanwhile, to obtain primary data, interviews were conducted using a questionnaire to 50 MSME actors with a sampling technique using proportional random sampling. Secondary data obtained through literature study. The analysis used is multiple linear regression. Based on the results of the study, there are several factors that influence financial literacy, namely age, level of formal education, and business turnover